Analysis of the content of the mathematics textbook for the fifth grade of primary school according to the standards (Mathematics Curriculum document (Journal of the College of Basic Education, 2022)
The aim of the research is to analyze the content of the mathematics textbook for the fifth grade of primary school according to the standards of the Mathematics Curriculum Document. From this goal, two questions were derived:What are the standards of the mathematics curriculum document that should be available in the content of the mathematics textbook for the fifth grade in the areas of (number and operations, algebra, geometry and measurement, statistics and probability(Are the standards of the mathematics curriculum document available in the content of a mathematics book for the fifth grade of primary school in the fields of (number and operations, algebra, geometry and measurement, statistics and probability( To achieve the goal of the research and answer the two questions, the researcher adopted the descriptive analytical approach, as the research sample was the mathematics book for the fifth grade of primary school for the academic year (2021-2022( As the researcher prepared a content analysis card in accordance with the standards of the mathematics curriculum document, verifying its validity after presenting it to a group of specialized arbitrators, as it obtained an agreement percentage of (88.51%(. The content analysis card, in accordance with the standards of the curriculum document in its final form, consisted of four areas: (the field of preparation and operations, which includes four axes and (125) indicators, and the field of algebra three axes and (29) indicators, and the field of geometry and measurement of three axes and (78) indicators The field of statistics and probability has two axes and (29) indicators. The mathematics textbook for the fifth grade of primary school was analyzed according to these criteria, and a sample of the analysis sample was presented to a number of specialized arbitrators and they agreed on the validity of the analysis process. The second was the use of other analysts and obtained an agreement ratio between analysts (0.93) using the Holste equation. The results of the research revealed that: The mathematics textbook for the fifth grade of primary school achieved a percentage of (63.60%) of the content standards of the mathematics curriculum document, as it achieved the first place in the field of preparation and operations with (78) indicators and (2168) recurrences and a rate of (65.34%), As for the field of engineering and measurement, it ranked second with (51) indicators and a rate of (715) recurrences and a rate of (21.55%), followed by the third rank in the field of statistics and probability, achieving (19) indicators and a rate of (220) recurrences and a rate of (6.63%), while the field of Al-Jabr ranked last with (18) indicators and (215) recurrences, or (6.48%(. Based on the research results, a number of recommendations and suggestions were presented.The most important recommendations:Benefiting from the list of criteria for the mathematics curriculum document for the current research, when making a change, developing, modifying, or avoiding deficiencies in the content of mathematics textbooks at the primary stage.Provide all primary school mathematics teachers with a copy of the mathematics curriculum document so that they have access to the content standards of the books that were designed in light of it.The most important suggestions:Conducting research in analyzing the content of mathematics textbooks for the intermediate or preparatory stage, according to the special mathematics curriculum document for each stage.Conducting comparative research for mathematics books for the primary stage in Iraq with mathematics books from Arab countries whose books were designed according to their own documents.